Bergey's Manual of Systematics of Archaea and Bacteria 2015
DOI: 10.1002/9781118960608.bm00023
|View full text |Cite
|
Sign up to set email alerts
|

The Revised Road Map to theManual

Abstract: The Second Edition of Bergey's Manual of Systematic Bacteriology (the “Systematics” ) represents a major departure from the First Edition, as well as from the Eighth and Ninth Editions of the Bergey's Manual of Determinative Bacteriology (the ‘Determinative” ), in that the organization of the content follows a phylogenetic framework based on analyses of the nucleotide sequence of the ribosomal small‐subunit RNA, rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…The bacteria that are able to decolourize textile azo dye were identified from several aspects including morphology characters and biochemical analysis as described in Bergey’s manual of determinative bacteriology (Garrity et al . 2005). The following biochemical tests, that is, Indole, Methyl Red, Voges‐Proskauer test, Citrate, Catalase, Oxidase, Nitrate Reduction test, Hydrolysis of Casein, Starch, Urea and Gelatin were performed.…”
Section: Methodsmentioning
confidence: 99%
“…The bacteria that are able to decolourize textile azo dye were identified from several aspects including morphology characters and biochemical analysis as described in Bergey’s manual of determinative bacteriology (Garrity et al . 2005). The following biochemical tests, that is, Indole, Methyl Red, Voges‐Proskauer test, Citrate, Catalase, Oxidase, Nitrate Reduction test, Hydrolysis of Casein, Starch, Urea and Gelatin were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary identification was based on its morphological and biochemical characteristics in addition to its carbohydrate fermentation profile following Bergey's Manual of Systematic Bacteriology (Garrity et al, 2005). Finally it was characterized according to its 16S rDNA sequence analysis.…”
Section: S Rrna Sequence Analysismentioning
confidence: 99%
“…Using a novel approach to both fix the derived coordinates and overlay subsets of sequences based on assigned names, we were able to quickly identify areas of disagreement between the existing nomenclature and the phylogenetic model. Scree plots revealed that the first three dimensions in the derived coordinate system accounted for Ͼ90% of the total variance, indicating the reliability of the projections (34,35). PCA also provided a unique view of the topology of bacterial and archaeal domains, which has remained remarkably stable, robust, and resistant to perturbation by different alignments, different implementations of PCA, or an almost 3-fold increase in the number of validly named species.…”
Section: Exploring Prokaryotic Taxonomy; Reconciliation Of the Nomencmentioning
confidence: 99%
“…Historically, our approach (6,(34)(35)(36) to reconciling nomenclature and 16S rRNA phylogeny was to employ methods from the field exploratory data analysis (37,38). Rather than relying on phylogenetic trees, which either lacked resolution when collapsed or were too unwieldy when viewed in full (Ͼ10,000 nodes), we applied principal-component analysis (PCA) to the 16S rRNA sequence data.…”
Section: Exploring Prokaryotic Taxonomy; Reconciliation Of the Nomencmentioning
confidence: 99%